The plethysm technique applied to the classification of nuclear states - Castilho Alcarás, J.A. [UNESP]; Tambergs, J.; Krasta, T.; Ruza, J.; Katkevicius, O. (Sociedade Brasileira de Física, 2002)
A short summary of the theory of symmetric group and symmetric functions needed to follow the theory of Schur functions and plethysms is presented. One then defines plethysm, gives its properties and presents a procedure for its calculation. Finally, some aplications in atomic physics and nuclear structure are given.